A student's guide to methodology - Clough, Peter; Nutbrown, Cathy (London : SAGE, 2012)
Essential for anyone undertaking a dissertation or thesis, this title presents clear and straightforward information and advice on the process and functions of methodology.
pt. I. Research is methodology. What is research? ; What is methodology? -- pt. II. The pervasive nature of methodology. Looking : seeing beyond the known ; Listening : issues of voice ; Reading : purpose and positionality ; Questioning : the focus of research -- pt. III. Making research public. Research design : shaping the study ; Reporting research : telling the story ; Research action : next steps.
Keywords: Education